Morphological and molecular phylogeny of the polycytopharyngeal ciliate Pycnothrix monocystoides Schubotz, 1908. Issue 1 (2nd January 2020) - Foissner, Wilhelm; Al-Rasheid, Khaled A. S.; Strüder-Kypke, Michaela C.; Lynn, Denis H.
Abstract : We reinvestigated Pycnothrix monocystoides Schubotz, 1908 from the intestine of the African Rock Hyrax ( Procavia capensis ) collected from Saudi Arabia, using protargol impregnation and electron microscopy. Pycnothrix is a unique, up to 5 mm long intestinal ciliate with about two million cilia and many cytostomes (i.e. actual cytostome plus cytopharynx; polycytopharyngy) in the oral furrow (∼vestibulum) that extends on both sides of the cell. Both walls of the furrow are covered by adoral membranelle-like ciliary polymerizations. To the right of the furrow and the cytostomes there are small ciliary fields, very likely homologous to the "dorsal brush" found in free-living litostomateans. The molecular investigations show Pycnothrix as sister to Balantidium and endemic Australian intestinal ciliates, e.g. the genus Bandia . We propose that the common ancestor had both an oral furrow and a special ciliary field both similar to that found in Balantidium . The unique morphology (polycytopharyngy) and the rather distinct molecular separation suggest maintenance of the family status given by Poche (1913 ).